Behavior, hormone, and gut microbiota change by YYNS intervention in an OVX mouse model - Lei, Huajuan; Liu, Jian; Deng, Juan; Zou, Pan; Zou, Zixiang; Li, Ziou; Li, Honghui; Luo, Lin; Tan, Zhoujin (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectPerimenopause depression disorder (PDD) is a very common problem in clinical practice and is characterized by depression and autonomic nervous symptoms, including hot flashes, palpitation, and night sweating. In addition, the comorbidity of menopause depression has long been an integral component of the estradiol (E2) shortage. Previous studies have suggested that the mechanisms underlying this comorbidity involved overlap of endocrine and cerebellar networks. Emerging evidence has shown that the endocrine–brain–gut–microbiota axis plays a key role in the regulation of affective disorders. Yangyin-ningshen formula (YYNS) is a traditional Chinese decoction tailored by Yijintang for menopausal depression intervention. Thus, we hypothesized that the YYNS may be involved in the menopause depression alleviation through the endocrine–brain–gut–microbiota axis.MethodsTo verify this, we constructed a bilateral ovariectomy (OVX) mouse model to simulate menopausal-related depression. Subsequently, behavioral tests including the open field test (OFT) and the forced swimming test (FST) were conducted to examine the depression state post-OVX. With YYNS or E2 intervention, enzyme-linked immunosorbent assay (ELISA) was used to determine the serum sex hormones level. 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS) were used to analyze the microbiome of the colon samples collected from mice in the sham surgery group (CSH), the OVX model group (CMD), the OVX with E2 hormone intervention group (CHM), and the OVX with YYNS intervention group (CYYNS). One week after OVX, CMD, CHM, and CYYNS showed depression in OFT, FST. Three weeks post-OVX, CHM and CYYNS showed a notable relief of depression; CMD shaped the OTUs shrinkage; and OTUs were raised in the sham, CHM, and CYYNS group. The CMD group showed that the abundance of Actinobiota decreased but that of Bacteriodia increased. The relative abundance of the genus varied in each group. Moreover, functional correlation of changes in sex hormone and gut microbes between different groups showed that the PRL level was negatively correlated with Odoribacter. T level was positively correlated with Lachnospiraceae NK4A136 group and Odoribacter abundance (p < 0.05).ConclusionOur results not only offer novel insights into the sex hormones and depression with OVX mice but also build an important basis for E2 or YYNS therapeutic efficacy on PDD, which provide for future research on this etiology through the endocrine–brain–gut–microbiota network.